What properly belongs to grammar? A response to Lepore and Stone. Issue 2 (17th February 2016) - Bezuidenhout, Anne
Abstract: Lepore and Stone devote Part I of their book to setting out a number of views that act as foils for their own positive 'disambiguation' view of interpretation developed in Part II. They divide their opposition into three camps: The Gricean rationalists, the neo-Gricean lexicalists, and the empirical psychologists. I try to show why a 'disambiguation' view of such phenomena is unappealing and why Relevance Theory provides a better account of these phenomena. I end with some brief remarks about what all of this tells us about the interface between semantics and pragmatics.